PENYEBAB TURNOVER INTENTION KARYAWAN PADA SEBUAH HOTEL (KRITIS, 2022)
The desire to leave an organization or the turnover intention of an employee always raises a big question mark, and the two main factors that usually drive the emergence of this desire are job insecurity and work stress experienced by the employee. The main purpose of this article is to determine the effect of job insecurity and work related stress (job stress) on the turnover intention felt by the employees of a hotel. The research that is used as the basis for writing this article uses Sudamala Suites & Villas Sanur which is located at Jalan Sudamala No. 20, South Denpasar, Denpasar City, Bali, as a case study. Data analysis techniques used include validity test, reliability test, multiple linear regression analysis, linearity test, normality test, heteroscedasticity test and multicollinearity test. The study found a positive and significant effect, both partially and simultaneously, between the independent variables, Job Insecurity and Job Stress, and the dependent variable, Turnover Intention, which clearly indicates that the higher the Job Insecurity and Job Stress felt by the employees of a hotel, the more turnover intention they have.